PENGARUH TEKNOLOGI PENGOLAHAN LAHAN TERHADAP PENDAPATAN DAN EFISIENSI USAHATANI KAKAO RAKYAT (Studi Kasus di Desa Sidomulyo Kecamatan Bakung Kabupaten Blitar) - Tanti Matus Sholeha; Yuli Hariyati (UNEJ e-Proceeding, 2018)
Sidomulyo village is one of the village in Bakung Sub-district, Blitar Regency which is a pilot center in the application of rorak technology. Rorak technology was originally a government program expected to be able to give increased production results. The increased production will affect farmers’ income getting higher. All farmers in Sidomulyo village initially implemented rorak technology, yet as time went on, only few farmers survived to implement the rorak technology. The objective of this research is to know (1) the income and cost efficiency of cocoa farming at rorak users and non-users in Sidomulyo Village, Bakung Sub-District, Blitar Regency. It had been conducted in Sidomulyo Village, Bakung Sub-District, Blitar Regency. The location was intentionally chosen (purposive method) by giving reasons that Sidomulyo Village is one of the cocoa center, and becomes one of the areas which is a pilot center of implementing rorak technology on cocoa farming. The sampling method had been performed by means of Proportionate Random Sampling, so 40 cocoa farmers were selected. The data used in this research were primary data obtained through interviews with questionnaires and secondary data. The data analysis method used was the income and efficiency of utilization farming costs performing independent sample t-test. The findings of this research indicated that the average income of rorak users cocoa farming was Rp 12,466,691.67 Rp/ha/year, while the average income of non-rorak users cocoa farming was Rp 12,138,854.0 Rp/ha/tahun. The average cost efficiency of rorak users farming was 6.37, while the efficiency cost of non-rorak users farming was 5.77, so that the value of the cost efficiency of rorak user farming was greater. The independent sample t-test showed that there was a significant difference between the cost efficiency of rorak user and non-rorak users cocoa farming in Sidomulyo Village, Bakung Sub-District, Blitar Regency.